Studi Fenomenologi: Praktik dan Makna Akuntansi bagi Wirausahawan Difabel Netra pada Usaha Mikro - Diska Arliena Hafni (Kompartemen : Jurnal Ilmiah Akuntansi, 2017)
This study explained the meaning and understand how accounting is practiced by blind entrepreneurs in micro businesses. Institutional theory is used as a basis for understanding the accounting practiced by blind entrepreneurs in micro businesses. This research is qualitative research with intepretive paradigm and used transcendental phenomenology method. Research data obtained through interviews and observations. Stages of data analysis consist of apoche, phenomenology reduction, variation of imagination, and synthesis of meaning and essence. The results showed that the Accounting practiced by bilnd entrepreneurs is in the form of financial records and memory. In this case, blind entrepreneurs prefer to remember rather than record. The meaning contained in accounting practices by blind entrepreneurs in micro businesses leads to the fulfillment of internal business information. It also hinted that accounting is practiced in accordance with the needs and abilities of the implementers. Keywords: Accounting Practice, Blind Entrepreneurs, Transcendental Phenomenology